Teaching and learning in environmental law pedagogy, methodology and best practice - Du Plessis, Anél; Fowler, Robert; Hamman, Evan; Warnock, Ceri; Kennedy, Amanda (Law teacher) (Cheltenham, [England] Edward Elgar Publishing Limited, 2023)
"This unique book focuses specifically on teaching and learning in environmental law, exploring innovative techniques, tools and technologies employed across the globe to teach this ever more important subject. Chapters identify particular challenges that environmental law poses for pedagogy, offering a mix of theory and practical guidance to legal scholars who are seeking to take up, or improve, their teaching of this subject. Providing an examination of teaching formats and methodologies that are both innovative and particularly adapted to the teaching of environmental law, contributions explore topics such as digital learning, joint teaching, flipped classrooms and scenario-based approaches, as well as discussing teacher-based, reflective, student-centred and research-based methods. The book also considers specific contexts for teaching environmental law such as specialized postgraduate programs, supervision methods for research students, teaching within non-law programs, and teaching online. Environmental law scholars at all levels of university instruction will find this book an invaluable opportunity to learn about new methods and approaches to teaching in this area. Its insights into legal teaching methodologies more broadly will also be of interest to legal academics in other areas of the law"--Provided by publisher.
From marginality to mainstream: the evolution of teaching and learning in environmental law / Rob Fowler [and four others] -- Engendering hope in environmental law students / Lynda Collins, Brandon D. Stewart -- Bringing the heart into environmental law teaching / Karen Bubna-Litic -- Placing natural resources law: preliminary thoughts on decolonizing teaching and learning about people, places, and law / Estair Van Wagner -- Is your textbook (still) really necessary? / Stuart Bell -- Techniques for enhancing the lecture format in teaching environmental law / Tracy Bach -- Teaching and learning environmental law using small group teaching methodologies / Ben Boer -- Enhancing learning in environmental law through assessment design / Ceri Warnock [and four others] -- Environmental law clinics in Australia and the United States: a comparison of design and operation / Evan Hamman, Jill Witkowski Heaps -- Game on! Game-based learning as an innovative tool for teaching international environmental law / Alexandre Lillo, Thomas Burelli -- Teaching international environmental law as a story / Chris McGrath -- The emergence of specialist postgraduate coursework programs in environmental law / Heather McLeod-Kilmurray -- Enriching the postgraduate environmental law classroom: combining mixed cohorts and intensive mode teaching / Erika Techera -- Doctoral research in environmental law (Part 1): rationale and some supervision challenges / Willemien du Plessis, Anâel du Plessis -- Doctoral research in environmental law (Part 2): the student-supervisor relationship / Anâel du Plessis, Willemien du Plessis -- Of density and decline: reflections on environmental law teaching in the UK and on the co-production of environmental law scholarship / Steven Vaughan -- Never mind the platform, heres the pedagogy: e-learning in environmental law / Amanda Kennedy, Amy Cosby -- Teaching environmental law in Thailand / Chacrit Sitdhiwej, Rob Fowler.
Paperback edition.
Includes bibliographical references and index.
Keywords: Environmental law -- Study and teaching